The trouble with marriage : feminists confront law and violence in India - Basu, Srimati (Gender and Justice., 2015)
"The Trouble with Marriage is part of a new global feminist jurisprudence around marriage and violence that looks to law as strategy rather than solution. In this ethnography of family courts and other crime and mediation settings in India, Srimati Basu reevaluates Indian feminist theories of marriage, gender violence, and the role of the state. Basu argues that alternative dispute resolutions, originally designed to empower women in a less adversarial legal environment, have created new subjectivities but have also reinforced oppressive socioeconomic norms that leave women no better off, individually or collectively. This volume examines the extent to which feminist visions of divorce, rape, and domestic violence law in India empower women and finds, paradoxically, that these alternative ideas actually reinforce women's economic and social inequality"--Provided by publisher